The Use of Gadget for Science Students of Semarang State University in the Millenial Era - Litasari Aldila Aribowo; Sigit Saptono; Bambang Subali; Putut Marwoto (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
This study aims to determine whether there is a relationship between the intensity of using gadgets from the Integrated Science Department of Semarang State University with the e-learning platform during lectures. This study uses a descriptive method and tries to analyze how the use of gadgets in the classroom. The steps to obtain data in the field were carried out by interviewing and distributing questionnaires to 80 students. The intensity of gadget utilization by students in the Millennial Era is classified as frequently used with evidence of 92.5% of respondents stating that they often use gadgets in their daily lives. They use gadgets for social media and look for information related to lecturing materials. The use of gadget-based learning models can be used as a learning strategy to attract the attention of students. The e-learning platform that has been known by Integrated Science students of Semarang State University as the most prospective millennial generation educator is Edmodo.